Bronkiektasis dan Emfisema pada Pasien Tidak Pernah Merokok dengan Riwayat Infeksi TB - Laporan Kasus: Laporan Kasus - Purwaka, Barlaam Bagus; Parikesit, Petra Gusti; Astuti, Merari Panti (Cermin Dunia Kedokteran, 2026)
Background: Bronchiectasis is a chronic lung disease characterized by permanent bronchial dilation and is commonly associated with previous respiratory infections. Structural airway damage may persist even after the primary infection has resolved, leading to chronic respiratory symptoms and progressive lung impairment. Tuberculosis (TB) is recognized as one of the major causes of post-infectious bronchiectasis, particularly in regions with a high prevalence of TB. Case: A 66-year-old female with a long history of tuberculosis presented with yellow sputum for two months. Chest CT scan showed fibrotic lines in both lungs, signs of bronchiectasis in the form of tram lines, and pulmonary emphysema. Previous chest x-rays revealed peribronchial and parenchymal infiltrates with a flattened diaphragm and emphysematous lung appearance. Discussion: Bronchiectasis with emphysema or chronic obstructive pulmonary disease (COPD) often occurs in the elderly population. A history of TB is a major risk factor for bronchiectasis occurring concurrently with COPD. Chronic inflammation due to TB infection can trigger further parenchymal damage manifesting as bronchiectasis and emphysema. Conclusion: This case report highlights the importance of radiological imaging in evaluating chronic respiratory symptoms in patients with a previous history of TB.